Systemic Inflammatory Response in Patients with Acetic Acid Poisoning - Quvatov Z. S; Abdurahmonov M. M. (International Journal on Integrated Education, 2022)
The authors investigated the interdependence of fibrinolysis activation and systemic inflammatory response syndrome development in 68 patients with severe level of acute poisoning by azaleptin. A positive correlation was found between blood levels of D-dimer, clinical indications of systemic inflammation and C-reactive protein.